The Concept of Lexicon Devoted to Silesian Culinary Art - Przymuszała, Lidia; Świtała-Trybek, Dorota (Studia Etnologiczne i Antropologiczne, 2019)
As far as Silesia is concerned the language and cuisine constitute fundamental and distinguishing factors of the Silesian ethnic group, they are the determinants of cultural identity and the symbol of cultural identification. The concept of perceiving the culinary art from two perspectives, cultural and linguistic one, was born taking the above into account. Culinary art, as a component of culture understood in a broad manner, serves as a significant element of the language system as well. It plays a crucial culture-forming role in human life and it has certain position in the semantic structure of language which is adequate to its rank. The lexicon of Silesian cuisine, which is being currently prepared, aims at collecting names of dishes in one publication, not only those which are still in use today and dishes recorded in the general consciousness of Silesians, but it also aims at archiving culinary vocabulary which is basically forgotten by presenting it in close connection with the culture of the aforementioned region